PERENCANAAN SISTEM INFORMASI STRATEGIS DELIVERY LAUNDRY DI KOTA YOGYAKARTA - Anisa Yulandari; Siti Fatonah (PROSIDING SNAST, 2018)
The rapid growth of the current economic and information technology systems, people are busy with routine work so don't have a lot of time to wash clothes. Employees and students who live in boarding houses spent much time outdoors so it has less time to perform washing and ironing, especially during the rainy season which will be difficult to dry the clothes. This condition is used by some people to open a laundry service. The rise of the laundry business does not only make it easy for customers to reach that service, but time limitations and the availability of motor vehicles makes customers cannot be delivering his clothes to where the laundry services. Therefore, it takes an application searches all at once between services – shuttles clothing from home to the place of laundry. The research for designing search applications and laundry as well as analyze business development strategy with the SWOT method and PIECES. The results of the analysis in the form of advice on the draft information technology infrastructure which can be implemented at the time of making the application searches and laundry. And some applications that need to be developed for the good use by every laundry business when the implementation can be done optimally and the development of HR management to implement the necessary applications.